The level, motives and functions of foreign reserves of the developed countries. Analysis with a particular focus on the European System of Central Banks - Bogołębska, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article concentrates on analysis of motives, level and functions fulfilled by foreign exchange reserves in developed countries, with special emphasis put on the dual system of reserves within Economic and Monetary Union (EMU). The foreign exchange reserves of industrial countries have grown up during the last decade. However, in the case of EMU this growth have been not due to the intentional policy of the central bank (as in the case of Japan and Switzerland), but due to positive changes of exchange rates and rates of return.